The Predominance of the French Language in Francophone African Literature: The Case of Konan Roger Langui’s Wandi Bla! - Kané, Métou (Literatūra, 2023)
Languages are equivalent in that they are, in essence, perceived as a means of communication within a given group. However, this primary functionality is not the essence of our thinking. It is, of course, important, but it includes a beyond that interests us: the representativeness of language on the literary chessboard. The latter seems crucial to us because, from an analytical point of view, it contributes to creating a hierarchy between the languages of the world. This fame is necessary for certain African cultures that thirst for literary expressiveness and whose languages are very often unknown at the level of world literature. And this is the basis of their inability to carry their rich culture into a process of accomplished literacy. The Baoulé language suffers from this deficiency. For example, Baoulé, Konan Roger Langui’s mother tongue, struggled to promote Attoungblan. This explains the poet’s choice of the French language as the language of writing in order to achieve this. This explains the poet’s choice of the French language as the language of writing in order to achieve this. Obviously, the scope of languages sometimes determines the choice of writers. Wandi Bla! attests to this. Through this poetic creation that puts orality at the service of writing, the work takes on an intercultural dimension.
Keywords: Attoungblan; Baoulé; French; promotion; literature